Uncovering exposures responsible for birth season – disease effects: a global study. (28th September 2017) - Boland, Mary Regina; Parhi, Pradipta; Li, Li; Miotto, Riccardo; Carroll, Robert; Iqbal, Usman; Nguyen, Phung-Anh (Alex); Schuemie, Martijn; You, Seng Chan; Smith, Donahue; Mooney, Sean; Ryan, Patrick; et al.
Abstract: Objective: Birth month and climate impact lifetime disease risk, while the underlying exposures remain largely elusive. We seek to uncover distal risk factors underlying these relationships by probing the relationship between global exposure variance and disease risk variance by birth season. Material and Methods: This study utilizes electronic health record data from 6 sites representing 10.5 million individuals in 3 countries (United States, South Korea, and Taiwan). We obtained birth month–disease risk curves from each site in a case-control manner. Next, we correlated each birth month–disease risk curve with each exposure. A meta-analysis was then performed of correlations across sites. This allowed us to identify the most significant birth month–exposure relationships supported by all 6 sites while adjusting for multiplicity. We also successfully distinguish relative age effects (a cultural effect) from environmental exposures. Results: Attention deficit hyperactivity disorder was the only identified relative age association. Our methods identified several culprit exposures that correspond well with the literature in the field. These include a link between first-trimester exposure to carbon monoxide and increased risk of depressive disorder ( R  = 0.725, confidence interval [95% CI], 0.529-0.847), first-trimester exposure to fine air particulates and increased risk of atrial fibrillation ( R  = 0.564, 95% CI, 0.363-0.715), and decreased exposure to sunlight during the third trimester and increased risk of type 2 diabetes mellitus ( R  = −0.816, 95% CI, −0.5767, −0.929). Conclusion: A global study of birth month–disease relationships reveals distal risk factors involved in causal biological pathways that underlie them.